LDL Impairs Endothelium-Dependent Relaxation especially in Hyperlipidemic Porcine Coronary Arteries - HAYASHI, Toshio; NAITO, Michitaka; KUZUYA, Masafumi; FUNAKI, Chiaki; ASAI, Kanichi; ISHIKAWA, Tomohiko; HIDAKA, Hiroyoshi; KUZUYA, Fumio (Dōmyaku kōka = The Journal of Japan Atherosclerosis Society, 1990)
We evaluated the effect of a low pathophysiological level of hyperlipidemia as well as the effect of in vitro exposure to LDL on the vascular responsiveness of isolated porcine coronary arteries. First, we fed pigs a cholesterol-rich diet for 4 weeks (C4 pigs) and 9 weeks (C9 pigs). The serum cholesterol level in the Cg pigs reached 218.5±32.9mg/dl compared with 85.5±8.4mg/dl in the controls. The Endothelium-dependent relaxation (EDR) caused by bradykinin, substance P, and serotonin were significantly reduced in the C9 pigs, but the relaxation induced by the Ca2+ ionophore, A23187 or nitroglycerin (NG) did not alter. Second, the direct effect of LDL in the presence of indomethacin was studied. The preincubation of LDL inhibited the EDR caused by bradykinin and A23187 especially in cholesterol-fed arteries, and also inhibited the EDR induced by substance P or serotonin in only cholesterol-fed arteries, not the control ones. The LDL did not affect the relaxation induced by the NG. These results suggest that EDR is attenuated by hyperlipidemia, and that the LDL directly attenuated the EDR especially in cholesterol-fed coronary arteries.